Productivity Improvement of Garments Industry by Implementing Line Balancing Algorithms—A Case Study - Mst. Anjuman Ara; Nafisa Anjum; Dilir Ahbab; Mushfica Takia Sidiika; Risat Rimi Chowdhury (Engineering Reports)
ABSTRACT Nowadays, the apparel industry is highly competitive worldwide and requires the correct application of industrial engineering techniques such as time study and line balancing techniques for productivity improvement. Productivity improvement in the readymade garments industry is mostly dependent on lead time as well as the cost of production. This research aims to recommend an effective layout and line‐balancing strategy so that downtime, process bottlenecks, the number of workstations, and the required number of personnel can be minimized to improve the efficiency of the production line. For this purpose, three different heuristics approaches named the Ranked Positional Weight (RPW) method, the Largest Candidate Rule (LCR), and the Kilbridge & Wester method are implemented for analyzing the production line. After the implementation of line balancing techniques, it was found that all three methods improved the line efficiency compared to the existing line efficiency. Among the three heuristics methods, the RPW method and LCR increased efficiency more compared to the Kilbridge and Wester method (KWM). By lowering the current 42 workstations to 23, the RPW method and LCR demonstrated an improvement in the line efficiency of the current hemming unit to 79.80% from 43.70%. The RPW approach or LCR will be effective in terms of efficiency in this particular situation. Finally, an efficient and improved balanced line is suggested with a new sequence of processes and an optimally designed layout which will minimize the idle time and manpower requirement. The derived results demonstrate that the devised model can effectively assist production managers in garment manufacturing organizations in managing line efficiency.